Resveratrol treatment may preserve the erectile function after radiotherapy by restoring antioxidant defence mechanisms, SIRT1 and NOS protein expressions - ATASOY, BESTE MELEK; ŞENER, GÖKSEL; TİNAY, İLKER; KAYA, ÖZLEM TUĞÇE; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (NATURE PUBLISHING GROUP, 2018)
Radiotherapy (RT) for prostate cancer (PC) can cause erectile dysfunction (ED) by damaging neurovascular structures with oxidative stress. In this study, we evaluated the effects of resveratrol, an antioxidant, on post-RT ED. Fifty rats in five groups were evaluated; control (C), prostate-confined radiotherapy with short- and long-term vehicle or resveratrol treatment. Cavernosal tissues were obtained to analyze glutathione (GSH), nitric oxide (NO), cyclic guanosine monophosphate (cGMP), 8-hydroxy-2'-deoxy-guanosine (8-OHdG) levels and superoxide dismutase (SOD), caspase-3 activities, sirtuin-1, Foxo-3, nNOS, and eNOS protein expressions. Intracavernosal pressures (ICP) were measured for the long-term treatment group. In the RT long-term vehicle treatment group, tissue GSH, NO, cGMP, and SOD activity were decreased while 8-OHdg levels and caspase-3 activities were increased. Radiotherapy caused a decrease in sirtuin-1, nNOS, and eNOS protein expressions. These parameters were reversed by resveratrol treatment. Foxo-3 protein expressions were unaltered in the RT + short-term vehicle treatment group and started to increase as a defense mechanism in the RT long-term vehicle group; however, resveratrol treatment caused a significant increase in Foxo-3 expressions. Resveratrol preserved the metabolic pathways involved in erectile function and provided functional protection. Resveratrol can be used as a supplementary agent in patients undergoing radiotherapy to preserve erectile function.
Keywords: RADIATION-THERAPY; PROSTATE-CANCER; RAT MODEL; OXIDATIVE STRESS; DIABETIC-RATS; DYSFUNCTION; PREVENTION; SILDENAFIL; CARCINOMA; TADALAFIL